BOOK REVIEW: Introduction to an ‟Introduction to Philosophy” (Edith Stein, Introducere în filosofie, trad. de Paul Gabriel Sandu, Opere complete 8, Editura Carmelitană, 2020) - TAT, Alin (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
The title of the book illustrates the protreptic genre, of the invitation to philosophy and seems to have the simplicity of essence. There will be at least two categories of readers interested in it: those who seek to understand the meaning of their existence and the world, from the perspective of the perplexities of their lives, but also those versed in philosophical readings and who have not lost the desire to resume initiation. It is known that introductions to philosophy are not always only introductory, but sometimes involve skillful approaches to prior understanding.